2010
DOI: 10.1158/0008-5472.can-10-1509
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Thioredoxin Reductase 1 Renders Tumors Highly Susceptible to Pharmacologic Glutathione Deprivation

Abstract: Tumor cells generate substantial amounts of reactive oxygen species (ROS), engendering the need to maintain high levels of antioxidants such as thioredoxin (Trx)-and glutathione (GSH)-dependent enzymes. Exacerbating oxidative stress by specifically inhibiting these types of ROS-scavenging enzymes has emerged as a promising chemotherapeutic strategy to kill tumor cells. However, potential redundancies among the various antioxidant systems may constrain this simple approach. Trx1 and thioredoxin reductase 1 (Txn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
108
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(117 citation statements)
references
References 46 publications
(60 reference statements)
7
108
0
Order By: Relevance
“…1E), in agreement with previous findings showing compensatory up-regulation of the GSH system in TrxR1 null cells (45).…”
Section: Oxidation Of Ptp1b But Not Shp2 Is Increased Insupporting
confidence: 93%
“…1E), in agreement with previous findings showing compensatory up-regulation of the GSH system in TrxR1 null cells (45).…”
Section: Oxidation Of Ptp1b But Not Shp2 Is Increased Insupporting
confidence: 93%
“…First, TR1 may serve to prevent cancer by maintaining cellular redox homeostasis and decreasing the rate of mutations that initiate tumor formation. At the same time, TR1 is required for tumor growth due to high susceptibility of cancer cells to oxidative stress (98,243,303). In a recent study, the dual role of TR1 in cancer has been further investigated using conditional knockout of TR1 in liver in a chemically induced model of hepatocarcinogenesis (47).…”
Section: Thioredoxin Reductasesmentioning
confidence: 99%
“…As time passes, more and more cell types are being found to replicate in the absence of TrxR1. Recently, it was shown that lymphomas lacking TrxR1 can initiate and progress normally in mice (Mandal et al, 2010), adding another cell type to the list of cell types that can replicate in the absence of TrxR1. Also, in investigations using a fluorescent marker-tagged system in which both copies of the TrxR1 gene were disrupted in an arbitrary population of all cell types in fetal mice, my group assessed which, if any, cell types failed to contribute to the adult mouse two months later.…”
Section: Requirements Of Disulfide Reductases For Replication In Rodementioning
confidence: 99%
“…In each case, the homozygous-mutant zygote proliferates to yield thousands of TrxR1-deficient cells prior to embryonic failure. Subsequently, using regulated disruption of these conditional alleles, mouse cells homozygous null for either allele have been shown to replicate vigorously (Mandal et al, 2010;Rollins et al, 2010), suggesting proliferation is normal in TrxR1-deficient cells. Why, then, do the mutant embryos die?…”
Section: Considerations Beyond Supplying Electrons To Rnrmentioning
confidence: 99%
See 1 more Smart Citation